Retrograde transgastric jejunostomy for nutritional management and aspiration prevention in cases with severe malignant esophageal strictures - Takeshi Yamashita; Koji Otsuka; Satoru Goto; Tomotake Ariyoshi; Kentaro Motegi; Masahiro Kohmoto; Akira Saito; Yoshihito Sato; Yutaka Kishimoto; Masahiko Murakami (DEN Open)
Abstract Locally advanced esophageal cancer often presents with dysphagia and can be complicated by aspiration pneumonia. Therefore, nutritional management is important to prevent pneumonia. Enteral nutrition via gastrostomies is common in esophageal cancer patients. Here, we describe the efficacy of nutritional management using a gastrojejunostomy tube retrogradely inserted in the esophagus through gastrostomy to simultaneously drain accumulated fluid on the proximal side of a malignant stricture. We performed this procedure for two cases with severe malignant strictures using two types of endoscope insertion. A 57‐year‐old male patient (Case 1) underwent a retrograde insertion of a gastrojejunostomy tube for severe esophageal malignant stricture with severe nausea and salivary reflux. After a narrow endoscope was inserted through the gastrostomy fistula, a gastrojejunostomy tube was inserted alongside a guidewire allowing the patient to undergo definitive chemoradiotherapy without symptoms. An 82‐year‐old male patient (Case 2) was scheduled for a minimally invasive esophagectomy following neoadjuvant chemotherapy after gastrostomy. However, the patient developed aspiration pneumonia due to salivary reflux; before surgery, a narrow nasal endoscope was inserted and passed through the strictures. The percutaneous endoscopic transgastric jejunostomy catheter was retrogradely inserted alongside the guidewire. In patients with malignant strictures and salivary reflux, retrograde insertion of gastrojejunostomy tubes can simultaneously provide enteral nutrition and saliva drainage.